Immunobiology of Merkel cell carcinoma. Issue 2 (March 2020) - Samimi, Mahtab; Kervarrec, Thibault; Touze, Antoine
Abstract : Purpose of review: Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer, which is associated in 80% of cases with the Merkel cell polyomavirus (MCPyV). Advanced stages respond to immune checkpoint inhibitors in 50% of cases. Major issues remain unanswered regarding its oncogenesis and optimal treatment. Recent findings: MCPyV-negative and MCPyV-positive MCCs have been hypothesized to derive from distinct cells, although the cell of origin remains a matter of debate. The crucial role the MCPyV small T oncoprotein was recently confirmed by its ability to inactivate p53, together with its contribution to the metastatic progression. In advanced cases, tumoral microenvironment may adequately predict responses to immunotherapies, and several mechanisms of primary and secondary resistance have been investigated. Summary: Identifying the mechanisms of oncogenesis allow experimentation of new therapeutic targets, which remain mandatory even at the era of immunotherapies. Although new insights in the mechanisms of primary and secondary resistance pave the way for development of further immunotherapy strategies, neoadjuvant strategies may challenge our whole approach of the disease.